Drought occurrence under future climate change scenarios in the Zard River basin, Iran - Pedram Mahdavi (IWA Publishing, 2021)
Global warming affected by human activities causes changes in the regime of rivers. Rivers are one of the most vital sources that supply fresh water. Therefore, management, planning, and proper use of rivers will be crucial for future climate change conditions. This study investigated the monitoring of hydrological drought in a future period to examine the impact of climate change on the discharging flow of the Zard River basin in Iran. Zard River is an important supplier of fresh and agricultural water in a vast area of Khuzestan province in Iran. A continuous rainfall-runoff model based on Soil Moisture Accounting (SMA) algorithm was applied to simulate the discharge flow under 10 scenarios (obtained from LARS-WG.6 software) of future climate change. Then, the Stream-flow Drought Index (SDI) and the Standard Precipitation Index (SPI) were calculated for each climate change scenario for the future period (2041–2060). The results of the meteorological drought assessment showed that near normal and moderate droughts had higher proportions among other drought conditions. Moreover, the hydrological drought assessment showed the occurrence of two new droughts (severe and extreme) conditions for the future period (2041–2060) that has never happened in the past (1997–2016). HIGHLIGHTS Examining two RCPs to evaluate runoff and precipitation in the future.; Using of Soil Moisture Accounting (SMA) to compute excessive rainfall and rainfall-runoff modeling.; Evaluating the interaction between SDI and SPI drought indices.; Five AOGCMs under two RCPs were tested in the drought monitoring.; Extreme droughts will occur in the future in this region and will decrease the water security.;